Temperature Monitoring System for Baby Incubator Based on Visual Basic - Abdul Latif; Afif Zuhri Arfianto; Joessianto Eko Poetro; Thanh Nguyen Phong; Elsayed T.Helmy (Universitas Muhammadiyah Yogyakarta, 2021)
An incubator room is conditioned to keep the temperature warm so the baby feels comfortable. A temperature monitor system for the incubator room placed separately from where the officer works is a hassle. It wastes time. Temperature detector design for infant incubator which has constant temperature is necessary. An LM35 sensor as a temperature detector was used in the design. The sensor was installed in a 100 x 80 cm room. The detected temperature was displayed on the LCD and computer in the staff room. Temperature (°C) is converted by an Arduino Uno microcontroller into an ADC (Analog Digital to Converter) value. Several LM35 sensors were mounted in rooms to detect the temperature. The LM 35 sensor was used by considering that it can be calibrated directly in the Celsius scale, a linear scale factor of 10mV/°C and has a temperature range between -55 ° C and 150 ° C.